Relationship Between Energy, Protein, Iron, and Calcium Intake with Hemoglobin Levels of Pregnant Women - Tuffahati Zalfa; Irawan, Andi Muh Asrul; Umami, Zakia; Rahmawati, Lusi Anindia; Yusuf, Andi Mukramin (Journal of Health and Nutrition Research, 2024)
Hemoglobin levels are a parameter that measures respiratory pigment in red blood cells. A decrease in hemoglobin levels can lead to anemia. Factors contributing to hemoglobin levels include inadequate nutrient intake, particularly iron and protein, as well as the effect of inhibitors on iron absorption such as calcium. This study aims to assess the intake of energy, protein, iron, and calcium in relation to hemoglobin levels among pregnant women. This research employs a Cross-Sectional study design. The sample consisted of 55 pregnant women selected through purposive sampling. Data collection on energy, protein, iron, and calcium intake was done using the SQ-FFQ questionnaire, while hemoglobin levels were measured using an Hb meter (EasyTouch GCHb), and data were analyzed using Spearman’s Rank Correlation test. The results showed that pregnant women had adequate energy intake (41.8%), excess protein intake (40%), adequate iron intake (89.1%), and adequate calcium intake (80%). Abnormal hemoglobin levels were observed in the third trimester of pregnancy (16.3%), whereas normal hemoglobin levels were found in the second trimester (34.5%). Statistical tests revealed no significant relationship between energy intake (p = 0.223), protein (p = 0.201), iron (p = 0.327), and calcium (p = 0.641) with hemoglobin levels. The conclusion of this study is that there is no significant relationship between energy, protein, iron, and calcium intake and hemoglobin levels among pregnant women in Parung Panjang District, Bogor Regency. Pregnant women should regularly consume calcium supplements and iron tablets to meet their iron and calcium needs, which can help prevent anemia.